THE INFLUENCE OF BPJS HEALTH SERVICE ACCESSIBILITY AND MEDICAL SERVICE QUALITY ON PARTICIPANT SATISFACTION LEVELS AMONG CIVIL SERVANTS IN SIMALUNGUN REGENCY - Khairani, Devia Astry; Nursantri Yantri; Kusmilawaty (International Journal of Cultural and Social Science, 2025)
One of the important benchmarks to evaluate the effectiveness of social security programs in the health sector is the level of participant satisfaction with BPJS Kesehatan. The purpose of this study was to determine how participant satisfaction among Civil Servants (PNS) in Simalungun Regency is influenced by the accessibility of BPJS Kesehatan services and the quality of health services. The methodology of this study is a survey strategy that uses a quantitative approach and questionnaires given to 100 PNS. EViews 12 software was used to analyze the data using multiple linear regression tests. The findings of the study indicate that, partially and simultaneously, participant satisfaction is positively and significantly influenced by the accessibility of services and the quality of medical services. More than half of the variation in participant satisfaction can be explained by these two variables, based on the coefficient of determination (R2) value of 54.45%. Therefore, BPJS and health facilities must continue to improve the quality and accessibility of medical services in order to increase participant satisfaction.